Feasibility study of combined dynamic imaging and lymphaticovenous anastomosis surgery for breast cancer-related lymphoedema. Issue 1 (8th October 2018) - Khan, A A; Hernan, I; Adamthwaite, J A; Ramsey, K W D
Abstract: Background: Breast cancer-related lymphoedema (BCRL) presents a significant healthcare burden and adversely affects quality of life of breast cancer survivors. A prospective feasibility study was performed on lymphaticovenous anastomosis (LVA) for the treatment of BCRL. Methods: Patients with BCRL underwent near-infrared spectroscopy with indocyanine green lymphatic mapping to identify suitable lymphatic channels for LVA. End-to-end anastomoses to subdermal venules were performed and patients recommenced compression garment therapy (CGT) after surgery. Volumetric assessment of the affected limb was performed at regular intervals using infrared perometry to calculate the excess volume reduction. Results: Over a 24-month interval, 27 patients with BCRL underwent LVA. The mean duration of lymphoedema was 3·5 (range 0·5–18) years, and the mean number of LVAs performed was 3 (range 2–5). Twenty-four of the 27 patients completed 12-month follow-up. Patients exhibited three patterns of volumetric response following LVA: sustained response (16 patients), transient response (5) or no response (6). Sustained responders showed an excess volume reduction of −33·2 per cent at 12 months, and this correlated positively with the number of LVAs performed ( r = −0·56, P = 0·034). Overall, ten patients were able to downgrade CGT after surgery, and two patients were CGT-free at 12 months. Conclusion: LVA resulted in a sustained volume reduction in selected patients and may offset the burden of CGT. Further work is required to identify biomarkers that predict a favourable response to LVA surgery. Abstract : Effective in selected patients